Toxicokinetics in rats and modeling to support the interpretation of biomonitoring data for rare-earth elements. (October 2021) - Desrosiers, Mathieu; Pelletier, Guillaume; Dieme, Denis; Côté, Jonathan; Jomaa, Malek; Nong, Andy; Bouchard, Michèle
Highlights: A physiological-based toxicokinetic model was developed for rare earth elements. Model parameters were derived from the literature and novel toxicokinetic data. Biomonitoring equivalents (BEs) are proposed. BEs are based on urinary levels corresponding to critical dose levels. The model and BEs provide rapid screening tools of populations for risk assessment. Abstract: Toxicokinetic models are useful tools to better understand the fate of contaminants in the human body and to establish biological guidance values to interpret biomonitoring data in human populations. This research aimed to develop a biologically-based toxicokinetic model for four rare earth elements (REEs), cerium (Ce), praseodymium (Pr), neodymium (Nd) and yttrium (Y), and to establish biomonitoring equivalents (BE) serving as biological guidance values. The model was constructed using physiological data taken from the literature as well as new experimental kinetic data. These new data indicated that REEs readily disappeared from blood and accumulated mostly in the liver; excretion occurred mainly through feces although a small fraction was eliminated in urine. To properly reproduce the observed kinetics, the model was represented as 19 compartments, which include main tissues and their components (such as retention by macrophages) supplied by blood, as well as routes of excretion. The transfer coefficients between compartments were determined numerically by adjustments to experimental data. Simulations gave good fits to available experimental kinetic data and confirmed that the same model structure is applicable to the four elements. BEs of 0.3 µg/L of Pr and Nd were derived from the provisional RfD of 0.5 mg/kg bw/day established by the U.S. EPA. These BEs can be updated according to new reference dose values (RfD). Overall, the model can contribute to a better understanding of the significance of biological measurements and to the inference of exposure levels; it can also be used for the modeling of other REEs. The BEs will further allow rapid screening of different populations using biological measurements in order to guide risk assessments.